Eddy interaction model for turbulent suspension in Reynolds-averaged Euler–Lagrange simulations of steady sheet flow. (January 2018) - Cheng, Zhen; Chauchat, Julien; Hsu, Tian-Jian; Calantoni, Joseph
Highlights: Eddy interaction model was implemented to the Reynolds-averaged Euler–Lagrange model to simulate turbulent suspension in sheet flow. The sediment diffusivity and Schmidt number are sensitive to the coefficient C0 associated with eddy interaction time scale. Reasonable sediment transport rates and transport layer thickness were predicted for a wide range of Shields parameters. Abstract: A Reynolds-averaged Euler–Lagrange sediment transport model (CFDEM-EIM) was developed for steady sheet flow, where the inter-granular interactions were resolved and the flow turbulence was modeled with a low Reynolds number corrected k − ω turbulence closure modified for two-phase flows. To model the effect of turbulence on the sediment suspension, the interaction between the turbulent eddies and particles was simulated with an eddy interaction model (EIM). The EIM was first calibrated with measurements from dilute suspension experiments. We demonstrated that the eddy-interaction model was able to reproduce the well-known Rouse profile for suspended sediment concentration. The model results were found to be sensitive to the choice of the coefficient, C 0, associated with the turbulence-sediment interaction time. A value C 0 = 3 was suggested to match the measured concentration in the dilute suspension. The calibrated CFDEM-EIM was used to model a steady sheet flow experiment of lightweight coarse particles and yielded reasonable agreements with measured velocity, concentration and turbulence kinetic energy profiles. Further numerical experiments for sheet flow suggested that when C 0 was decreased to C 0 < 3, the simulation under-predicted the amount of suspended sediment in the dilute region and the Schmidt number is over-predicted ( Sc > 1.0). Additional simulations for a range of Shields parameters between 0.3 and 1.2 confirmed that CFDEM-EIM was capable of predicting sediment transport rates similar to empirical formulations. Based on the analysis of sediment transport rate and transport layer thickness, the EIM and the resulting suspended load were shown to be important when the fall parameter is less than 1.25.